Disney princess: Sleeping beauty - BPI India (New Delhi)
Parent and Child Read Together is a series of books for young readers who love reading and wish to inculcate important reading skills. Parents will share a unique reading experience with their children that will help children develop reading and comprehension skills. Complemented with breathtaking illustrations that infuse life into the characters, the books in this series are each remarkable and take young children into the world of fantasy, adventure, illusion, fairies and magic with emotions as diverse as love, hatred, misery, anguish, affection and joy. Sleeping Beauty is an engaging story of a princess who is cursed to eternal slumber by a wicked witch.
Location: 3D
Keywords: Fiction book